The efficacy and safety of ATR inhibitors in the treatment of solid tumors: a systematic review and meta-analysis - Su, Yaxu; Lu, Xinyu; Bu, Zhenzhen; Yang, Xue; Liu, Ping (Frontiers in Oncology, 2025)
Ataxia telangiectasia and Rad3-related kinase (ATR) is a central regulator of the DNA damage response and a promising therapeutic target in tumors with genomic instability. This meta-analysis evaluated the efficacy and safety of ATR inhibitors in patients with solid tumors. A systematic search of PubMed, Embase, and major Chinese and international databases up to September 2025 identified ten clinical trials including 810 patients treated with ATR inhibitors as monotherapy or in combination. Outcomes assessed included objective response rate, disease control rate, progression-free survival, overall survival, and treatment-related adverse events. Pooled analyses showed no significant overall improvement in efficacy endpoints compared with standard therapies. However, subgroup analysis demonstrated marked benefit in non-small cell lung cancer, with significantly prolonged progression-free survival and overall survival, while efficacy in other tumor types was minimal. The overall risk of adverse events was comparable to control groups, although hematologic toxicities such as myelosuppression (pooled RR = 1.04) and neutropenia (pooled RR = 1.34) were common. These findings suggest that ATR inhibitors may be particularly effective in non-small cell lung cancer and selected ovarian cancer subgroups, but further biomarker-driven randomized trials are required to confirm their clinical value and optimize patient selection.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251123612.